SARS-CoV-2 Omicron is an immune escape variant with an altered cell entry pathway - Willett, Brian J.; Grove, Joe; MacLean, Oscar A.; Wilkie, Craig; De Lorenzo, Giuditta; Furnon, Wilhelm; Cantoni, Diego; Scott, Sam; Logan, Nicola; Ashraf, Shirin; Manali, Maria; Szemiel, Agnieszka; et al. (Nature microbiology, 2022)
Vaccines based on the spike protein of SARS-CoV-2 are a cornerstone of the public health response to COVID-19. The emergence of hypermutated, increasingly transmissible variants of concern (VOCs) threaten this strategy. Omicron (B.1.1.529), the fifth VOC to be described, harbours multiple amino acid mutations in spike, half of which lie within the receptor-binding domain. Here we demonstrate substantial evasion of neutralization by Omicron BA.1 and BA.2 variants in vitro using sera from individuals vaccinated with ChAdOx1, BNT162b2 and mRNA-1273. These data were mirrored by a substantial reduction in real-world vaccine effectiveness that was partially restored by booster vaccination. The Omicron variants BA.1 and BA.2 did not induce cell syncytia in vitro and favoured a TMPRSS2-independent endosomal entry pathway, these phenotypes mapping to distinct regions of the spike protein. Impaired cell fusion was determined by the receptor-binding domain, while endosomal entry mapped to the S2 domain. Such marked changes in antigenicity and replicative biology may underlie the rapid global spread and altered pathogenicity of the Omicron variant. The Omicron variant evades vaccine-induced neutralization but also fails to form syncytia, shows reduced replication in human lung cells and preferentially uses a TMPRSS2-independent cell entry pathway, which may contribute to enhanced replication in cells of the upper airway. Altered fusion and cell entry characteristics are linked to distinct regions of the Omicron spike protein.